Who Says Only Men Have a Beard?: Revisiting the Question of Gender Ambiguity in Persian Poetry. Issue 2 (1st December 2021) - Montazeri, Fateme
Abstract: The presence of male homoeroticism in Persian poetry has long been noted. This sexual configuration is largely based on the conventional manner in which the beloved is described with male attributes, including a hairline above the lips or sideburns. Such readings assume a direct relationship between poetic topoi and external reality, and project, ahistorically, a modern aesthetic assumption onto premodern gender norms. This article argues that a male-associated rendition of the beloved, specifically in the case of the rhetorics of the facial hair that permeates the description of patrons, the divine and women alike, reveals not necessarily the sweetheart's gender, but dominant perceptions of praiseworthy characteristics and the power dynamics that rule the rhetorics of premodern gender norms.